Brief Report: Exploratory Evaluation of Clinical Features Associated with Suicidal Ideation in Youth with Autism Spectrum Disorder - Ellison, Kimberly S.; Jarzabek, Elzbieta; Jackson, Scott L. J.; Naples, Adam; McPartland, James C. (Journal of Autism and Developmental Disorders, 2022)
There has been a heightened awareness of an increased risk of suicidality among individuals with autism spectrum disorder (ASD) due to high rates of suicidal ideation (SI) in this population (11–66%). The current study investigated the rate of parent-endorsed SI and associated clinical features in 48 youths with ASD (Age; M: 12.97 years, SD: 2.33). SI was endorsed in 18.75% of participants. Youth with SI exhibited significantly higher levels of affective problems, externalizing problems, feelings of humiliation and rejection, and symptoms related to perfectionism. Results indicate that co-occurring mental health problems are associated with suicidal ideation and provide relevant targets for psychotherapeutic intervention. This preliminary study in a modest sample suggests the value of further research in larger samples to replicate and generalize these findings.
Keywords: Autism spectrum disorder; Risk factors; Suicidal ideation; Suicide risk; Youth; dept.adm; peer-reviewed

An Introduction to Autism and the Autism Spectrum - Volkmar, Fred R.; Jackson, Scott; Pete, Brian (Handbook of Autism Spectrum Disorder and the Law, 2021)
The syndrome of infantile autism was identified in 1943 (although cases clearly were present earlier). Very quickly there began to be a debate about the nature of autism and the boundaries of the autism phenotype. In the 1970s multiple lines of evidence emerged to suggest that autism should be recognized as a disorder in its own right and this happened in 1980. Since that time there has been an explosion of research and the debate about the boundaries of the diagnostic concept has continued. It does appear that individuals on the autism spectrum present special issues and challenges in terms of their interactions with the legal system at all levels. In this chapter we summarize the state of scientific knowledge and highlight some important areas relevant to those who deal with individuals with autism in legal settings.
Keywords: Asperger’s; Autism; Autism spectrum disorder; Diagnosis; dept.adm

Brief Report: A Specialized Fitness Program for Individuals with Autism Spectrum Disorder Benefits Physical, Behavioral, and Emotional Outcomes - Jackson, S.L.J.; Abel, E.A.; Reimer, S.; McPartland, J.C. (Journal of Autism and Developmental Disorders, 2022)
Individuals with autism spectrum disorder (ASD) engage in less physical activity than typically-developing peers. This can result in serious negative consequences for individual well-being and may contribute to the physical, behavioral, and emotional challenges associated with ASD. This study explored the potential benefits of trainer-led, individualized, physical fitness sessions specialized for ASD. Eleven individuals (ages 7–24 years) with ASD were assessed at baseline and following 15 fitness sessions. Participants demonstrated improvements in core and lower-body strength and reductions in restricted and repetitive patterns of behavior, along with non-significant but marked reductions in issues with daytime sleepiness. Results suggest the merit of specialized fitness programs and emphasize the need for larger and more rigorous research studies on this topic. © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.
3 citations (Crossref) [2023-10-31]
Keywords: Autism spectrum disorder; Exercise; Fitness; Physical health; Restricted and repetitive behaviors; Sleep behaviors; dept.aa; dept.adm; peer-reviewed

Mood Disorders in High-Functioning Autism: The Importance of Alexithymia and Emotional Regulation. - Morie, Kristen P; Jackson, Scott; Zhai, Zu Wei; Potenza, Marc N; Dritschel, Barbara (Journal of Autism and Developmental Disorders, 2019)
Individuals with autism spectrum disorder (ASD) often have co-morbid anxiety and depression. Alexithymia and emotion regulation difficulties are commonly seen in individuals with ASD and in mood disorders. We hypothesized that alexithymia and emotional regulation would mediate the relationship between autistic features and anxiety/depression symptom severity. We collected data about emotional regulation, alexithymia, autistic symptoms and depression/anxiety in a sample of 64 young adults with ASD. We constructed two serial multiple mediator models, using autistic features as the independent variable and anxiety/depression symptoms as outcome variables. The serial relationship between alexithymia and emotional regulation mediated associations between autistic features and depression and anxiety, separately. The findings suggest that targeting alexithymia may benefit therapies designed to alleviate mood disorders in ASD.
43 citations (Crossref) [2023-10-31] Place: United States Morie, Kristen P. Department of Psychiatry, Yale University School of Medicine, New Haven, CT, 06510, USA. kristen.morie@yale.edu. Morie, Kristen P. Child Study Center, Yale University School of Medicine, New Haven, CT, 06510, USA. kristen.morie@yale.edu. Jackson, Scott. Department of Psychiatry, Yale University School of Medicine, New Haven, CT, 06510, USA. Scott.Jackson@yale.edu. Jackson, Scott. Child Study Center, Yale University School of Medicine, New Haven, CT, 06510, USA. Scott.Jackson@yale.edu. Jackson, Scott. Office of Assessment and Analytics, Southern Connecticut State University, 501 Crescent Street, New Haven, CT, 06515, USA. Scott.Jackson@yale.edu. Zhai, Zu Wei. Department of Psychology, Middlebury College, Middlebury, VT, 05753, USA. Potenza, Marc N. Department of Psychiatry, Yale University School of Medicine, New Haven, CT, 06510, USA. Potenza, Marc N. Child Study Center, Yale University School of Medicine, New Haven, CT, 06510, USA. Potenza, Marc N. Department of Neuroscience, Yale University School of Medicine, New Haven, CT, 06510, USA. Potenza, Marc N. Connecticut Council on Problem Gambling, Wethersfield, CT, 06109, USA. Potenza, Marc N. Connecticut Mental Health Center, New Haven, CT, 06519, USA. Dritschel, Barbara. School of Psychology & Neuroscience, University of St Andrews, St. Andrews, Fife, KY16 9JP, UK.
Keywords: *Affective Symptoms/px [Psychology]; *Autism Spectrum Disorder/px [Psychology]; *Emotions; *Mood Disorders/px [Psychology]; ASD; Adolescent; Adult; Affective Symptoms; Affective Symptoms/ep [Epidemiology]; Aged; Alexithymia; Anxiety; Anxiety Disorders; Article; Asperger Syndrome; Asperger syndrome; Autism; Autism Spectrum Disorder; Comorbidity; Depression; Emotional regulation; Emotions; Female; Humans; Male; Middle Aged; Mood Disorders; Mood disorders; Self Report; Surveys and Questionnaires; Toronto Alexithymia scale; Young Adult; adolescent; adult; aged; alexithymia; anxiety; anxiety disorder; autism; comorbidity; controlled study; depression; dept.aa; dept.adm; emotion; emotional disorder; emotionality; female; human; major clinical study; male; mental health; middle aged; mood disorder; peer-reviewed; priority journal; psychology; questionnaire; self report; young adult